2012
DOI: 10.1111/j.1468-3083.2012.04542.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of human papillomaviruses in persistent and glucocorticoid‐resistant juvenile phimosis

Abstract: Our prospective study has provided evidence that HPV is not usually present in the foreskin of boys with persistent phimosis after their first year of life and that topical glucocorticoid treatment failure is not associated with HPV or any specific histopathological changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
(101 reference statements)
0
14
0
1
Order By: Relevance
“…In this regard, HPV transmission may occur upon contact with infected towels or other objects. In contrast to these findings, Pilatz et al [15] did not find HPV in the foreskin of boys.…”
Section: Hr-hpv Transmission Among Sexual Partnersmentioning
confidence: 75%
See 1 more Smart Citation
“…In this regard, HPV transmission may occur upon contact with infected towels or other objects. In contrast to these findings, Pilatz et al [15] did not find HPV in the foreskin of boys.…”
Section: Hr-hpv Transmission Among Sexual Partnersmentioning
confidence: 75%
“…Models have shown that HPV transmissibility is substantially higher than that of other viral sexually transmitted pathogens [13], but data on the natural history of HPV transmission between heterosexual partners are limited. Many studies [14][15][16][17] analyzed the prevalence and genotypes of high-risk infections of the foreskin before first sexual intercourse found asymptomatic infection in 12-83.3% [14,16], speculating that non-sexual routes play significant roles in HPV transmission. In this regard, HPV transmission may occur upon contact with infected towels or other objects.…”
Section: Hr-hpv Transmission Among Sexual Partnersmentioning
confidence: 99%
“…The DNA concentration was determined with a Nanodrop 2000 (Thermo Scientific, Wilmington, DE, USA). Per case, 50 ng DNA was analysed with PCR for 32 high-and low-risk HPV (types 6,11,16,18,31,33,35,39,42,44,45,[51][52][53][54]56, 58, 59, 61, 62, 66-68, 70, 72, 73, 81-84, 90, 91) as previously described [28]. A chip-based LCD Array HPV Kit was used according to the manufacturer's instructions (Chipron, Berlin, Germany).…”
Section: Analysis Of Hpv Infectionmentioning
confidence: 99%
“… 18 Austria 121 NA (0.0–10.0) NA 6, 11, 16, 18 98 55 43 55 NA NA Pilatz et al . 16 Germany 82 4.1 (1.0–14.0) 82 6, 11, 16, 18, 31, 33, 35, 39, 42, 44, 45, 51–54, 56, 58, 59, 61, 62, 66–68, 70, 72, 73, 81–84, 90, 91 0 0 0 0 0 0 Martino et al . 17 Austria 50 5.5 (0.42–15) NA 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59 6 6 0 6 6 0 Verit et al .…”
Section: Resultsmentioning
confidence: 99%